Effects of online learning on responsibility character of junior high school students in Yogyakarta - Saliman Saliman; Agustina Tri Wijayanti; Yumi Hartati (Jurnal Cakrawala Pendidikan, 2023)
This study aims to confirm the results of online learning for junior high school students in Yogyakarta and to clarify the impact of online learning on the development of character values. This study uses a mixed method that combines qualitative and quantitative methods. The research data were obtained by distributing questionnaires to 44 students in 249 public schools. The data collected were tabulated and analyzed to determine the effects of online learning on the responsibility character of junior high school students in Yogyakarta. The results show that the R-squared value of 0.107 impacts liabilities of 10.7 so the remaining 89.3 liabilities are influenced by other variables not included in this survey model. Hypothesis test proves that t count 2,590 t-table 1,6725 counts and significance 0.012 0 F-table 4.01 and significance 0.012 0.050. To conclude, online learning affects your sense of responsibility at the same time.